2012
DOI: 10.1007/s11010-012-1501-x
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of rosiglitazone on myocardium Glut-4 mRNA expression during ischemia–reperfusion injury in cardio-pulmonary bypass in dogs

Abstract: During cardiac pulmonary bypass (CPB), myocardial ischemia-reperfusion (I/R) induces heart glucose metabolism impairment. Our previous research showed that the decreased glucose utilization is due to decreased glucose transporter-4 (Glut-4) expression and translocation to myocyte surface membranes. This study further examined whether rosiglitazone, a synthetic agonist of peroxisome proliferator-activated receptor γ, could intervene glucose metabolism by regulating Glut-4 mRNA during I/R in dogs. Cardiac ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…137 More recently, TZD administration was reported to increase GLUT4 expression, improve insulin sensitivity, and enhance cardiac function in dogs. 138 However, clinical use of PPAR-γ agonists to treat heart failure, cardiac ischemia/reperfusion, and even diabetes has been hindered due to potential cardiac toxicity manifested as fluid retention. 139 …”
Section: Metabolic Therapy For the Failing Heartmentioning
confidence: 99%
“…137 More recently, TZD administration was reported to increase GLUT4 expression, improve insulin sensitivity, and enhance cardiac function in dogs. 138 However, clinical use of PPAR-γ agonists to treat heart failure, cardiac ischemia/reperfusion, and even diabetes has been hindered due to potential cardiac toxicity manifested as fluid retention. 139 …”
Section: Metabolic Therapy For the Failing Heartmentioning
confidence: 99%
“…During reperfusion following a prolonged ischemia, the expression of glucose transporter-4 was inhibited significantly, leading to decreased glucose uptake, impaired energy metabolism, and cardiac function damage. The addition of rosiglitazone into cardioplegic solution increased expression of glucose transporter-4 at mRNA level and resulted in the attenuation of myocardium damage, alleviation of insulin resistance [115].…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Cardiopulmonary bypass (CPB)‐induced cardiac injury is one of the most serious forms of critical illness, which is characterized by stress, hyperglycemia, inflammation, hyperactive metabolic responsiveness, and glucose metabolism disorders . It has been shown that impaired myocardial glucose uptake results in myocardial damage and cardiac dysfunction in myocardial ischemia/reperfusion injury or in diabetes .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Cardiopulmonary bypass (CPB)-induced cardiac injury is one of the most serious forms of critical illness, which is characterized by stress, hyperglycemia, inflammation, hyperactive metabolic responsiveness, 9,10 and glucose metabolism disorders. 11 It has been shown that impaired myocardial glucose uptake results in myocardial damage and cardiac dysfunction in myocardial ischemia/ reperfusion injury or in diabetes. 7,12 Moreover, acute myocardial insulin resistance has been shown to play an important role in cardiac dysfunction and increases the complications and mortality in an animal model of severe burn injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation